GENERAL CULTURAL COMPETENCE OF A TEACHER AS A COMPONENT OF HIS PEDAGOGICAL CULTURE - Yakubova Feruza Yusufovna (Western European Studies, 2023)
As the scientific and theoretical level and information richness of the content of education in secondary school increases, the need grows to improve not only the psychological, pedagogical and scientific-subject knowledge of teachers, but also to improve their cultural training, equipping them with the knowledge necessary to understand the sociocultural context of the science being taught. For teachers in modern conditions, it is especially important to combine the depth of knowledge in the subject with broad erudition in other areas of human activity. In this regard, an important condition for increasing the level of teachers’ pedagogical culture is the development of their general cultural competence, which in our study is interpreted as a personal and professional characteristic of a teacher, showing his preparedness and readiness to introduce students to the cultural context of the subject being taught. The purpose of the article is to identify the essence of a teacher’s general cultural competence, theoretically substantiate the pedagogical conditions for its development, and determine its influence on the success of teaching activities.
Keywords: competence; appearance; pedagogical